Librarians’ Perceptions of Tribalism/Ethnicity and Favouritism Practices and the Perceptions’ Effect on Job Satisfaction and Service Delivery in Federal University Libraries in Southern Nigeria - Omosekejimi, Ademola Ferdinand; Nweke, Angela Chiwendu; Nwobu, Benjamin Kenechukwu (Evidence Based Library and Information Practice, 2024)
Objective – This study examined librarians’ perceptions of tribalism/ethnicity and favouritism practices and the perceived effect on job satisfaction and service delivery in federal university libraries in Southern Nigeria. The study was aimed at observing whether or not librarians perceive that their senior library managers engage in tribalism/ethnicity and favouritism practices; discerning the extent to which they are perceived to be engaging in tribalism/ethnicity and favouritism practices; ascertaining how the perceived tribalism/ethnicity and favouritism practices can affect job satisfaction of librarians and service delivery by librarians in federal university libraries in Southern Nigeria.Methods – This study used a descriptive survey research design. The total population for this study comprised 296 librarians who were below the rank of senior library manager from 18 federal university libraries in the southern region of Nigeria. A structured questionnaire was used for data collection. The data collected for this study were analyzed using simple percentage/frequency counts and weighted mean.Results – This study found that librarians in university libraries in Southern Nigeria believe that senior library managers engage in tribalism/ethnicity and favouritism practices and that the extent of these practices is very high. These librarians clearly have strong concerns that the practise of tribalism/ethnicity and favouritism in libraries can have negative effects on librarians’ job satisfaction and can lead to poor service delivery.Conclusion – It is glaring from this study that tribalism and favouritism practices by senior library managers are perceived to be prevalent in university libraries in Southern Nigeria, significantly impacting librarians' job satisfaction. This negative workplace dynamic can hinder effective service delivery, ultimately affecting user experience and the library's role in education. Addressing these biases is crucial, as promoting fairness and inclusivity can enhance job satisfaction, improve staff morale, and lead to higher quality library services for all patrons.